Investment projects and changes in prices of landed properties as reflected in the cadastral value - Siejka, М. (Видавництво Національного університету "Львівська політехніка", 2007)
Methods of determination of cadastral value have been widely discussed in the literature for a dozen or so years. \ n each case what is proposed is the application of the mass valuation method based on the analysis of transaction prices which characterise the so-called local market. \ n such a situation the attributes that affect the cadastral value are the attributes which influence transaction prices. One of the attributes which play the most important role in price formation is the location of a given real property and, hence, its surroundings and neighbourhood. This article is an attempt to carry out an analysis to show the impact of new investment projects on the level of prices of land situated in the vicinity of such projects.